TINJAUAN ANALISIS PRINSIP ULTRA VIRES TERHADAP PERTANGGUNGJAWABAN HUKUM DIREKSI PERSEROAN TERBATAS ATAS KEPAILITAN PERUSAHAAN - Mayzura Kamila Sukma; Gracia Tirta Imanuela; Adinda Thalia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The principle of ultra vires is an important legal concept in the corporate context, particularly regarding the authority and legal responsibility of the board of directors. In Indonesian law, this principle refers to actions taken by a corporate body or its organ that exceed the authority granted by the company’s articles of association or applicable regulations. This article aims to analyze the application of the ultra vires principle within the framework of corporate law, specifically in the context of the directors' legal responsibility related to corporate bankruptcy under Law No. 40 of 2007 on Limited Liability Companies (UU PT) and Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (UU Kepailitan). This research uses a normative (doctrinal) approach, with an analysis of applicable laws, legal doctrines, and relevant court decisions. The findings indicate that although the ultra vires principle faces challenges in its application within Indonesian legal practice especially due to a lack of clarity regarding actions that exceed the authority of directors this principle still plays a crucial role in assessing the legal responsibility of directors in bankruptcy cases. Actions that are deemed ultra vires by the directors may lead to civil liability, and even criminal liability, if they cause harm to the company and creditors.